Peningkatan Derajat Kesehatan Masyarakat Melalui Pemeriksaan Kesehatan Gratis di Dusun Bukit Tinggi Desa Dete Kecamatan Lape Tahun 2022 - herni Hasifah; Iga Maliga (AMMA : Jurnal Pengabdian Masyarakat, 2022)
Degenerative disease is caused by a decrease in the function of the body's organs. Some degenerative diseases, namely hypertension, coronary heart disease, diabetes mellitus, gout, etc. Many things are the cause of the development of degenerative diseases, including: unhealthy lifestyles such as smoking, lack of exercise and stress. The trend of degenerative diseases is increasing day by day. Prevention of degenerative diseases can be above by means of health screening at the age of 30 years. Health problems happened in Dusun Bukit Tinggi RT 001 RW 010 Dete Village, among others hypertension and diabetes mellitus. This activity involves students as technical implementing assistants. Activity was carried out in March in the Dusun Bukit Tinggi, RT 001 RW 010, Dete Village, Lape District, Sumbawa Regency. Activities are carried out using the door to door method. This activity goal to improve health status through health checks and increase public knowledge by presenting information about degenerative diseases.